Wpływ Ujemnej Krzywizny Wykresu σ = σ(ε) na Parametry Fali Naprężenia w Gruncie - Włodarczyk, E. (Engineering Transactions, 1971)
In this paper, a closed analytical solution is obtained for the wave problem of the unloading of a week discontinuity propagated in the friable, dry ground, approximated by a curvilinear characteristic σ = σ(ε) with a negative curvature (d^2 σ/de^2<0,σ<0,ε<0), and with rigid unloading. On the basis of this solution, an extensive numerical analysis of the problem is performed, and the conditions established at which it is possible to apply the linear approximation of the wave-front of unloading as well as the linear change of the stress with time in the loading zone.